The Ottoman Crimean War (1853-1856) - Badem, Candan (The Ottoman Empire and its Heritage, 2010)
This book analyzes the Crimean War from the Ottoman perspective based mainly on Ottoman and Russian primary sources, and includes an assessment of the War's impact on the Ottoman state and Ottoman society. Readership: All those interested in the Crimean War, military history, Ottoman history, European history and Russian history.